2004
DOI: 10.1002/art.20337
|View full text |Cite
|
Sign up to set email alerts
|

Outer surface lipoproteins ofBorrelia burgdorferivary in their ability to induce experimental joint injury

Abstract: Objective. To examine the ability of bacterial lipoproteins from the spirochete Borrelia burgdorferi to cause in vivo tissue injury (arthritis).Methods. Outer surface proteins (OSPs) from B burgdorferi were used in a rat model of antigen-induced allergic arthritis. Intraarticular challenge with recombinant OspA, OspB, and OspC in nonlipidated (peptide) and lipidated forms was performed in the left knee joint; the contralateral joint received buffer as control. Inflammation was monitored by technetium scintigra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 55 publications
(47 reference statements)
1
20
0
Order By: Relevance
“…Although the exact etiology of treatment-resistant Lyme arthritis is not known, some investigators believe that an OspA-induced autoimmune reaction is responsible for this condition (1,2,12,18). An arthritic reaction to OspA has also been shown in rats (5), suggesting that constitutive OspA production might lead to higher levels of arthritis. A study by Yang et al (28) showed that an OspAB-negative mutant actually caused a more pronounced arthritis than the wild-type strain, suggesting that OspA is not linked to arthritis in the murine model of Lyme disease.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Although the exact etiology of treatment-resistant Lyme arthritis is not known, some investigators believe that an OspA-induced autoimmune reaction is responsible for this condition (1,2,12,18). An arthritic reaction to OspA has also been shown in rats (5), suggesting that constitutive OspA production might lead to higher levels of arthritis. A study by Yang et al (28) showed that an OspAB-negative mutant actually caused a more pronounced arthritis than the wild-type strain, suggesting that OspA is not linked to arthritis in the murine model of Lyme disease.…”
Section: Discussionmentioning
confidence: 92%
“…Despite the apparent lack of OspA production in rodents, signals present at sites of inflammation in the murine model have been shown to increase OspA production (9). In addition, lipidated OspA injected into rat joints caused arthritis (5). In summary, a large body of work supports the view that B. burgdorferi OspA is primarily a protein that is expressed in the vector for attachment of spirochetes to the tick gut epithelium.…”
mentioning
confidence: 91%
“…These components can cause neuropsychiatric manifestations such as lymphocytic meningitis, cranial and peripheral neuropathy, and cerebral infarcts [29,30]. When compared to LPS, bacterial lipoproteins activate inflammatory pathways more vigorously [31], leading to more severe damage to tissue [32]. Bacterial lipoproteins still remain in the tissue even after the degradation of bacteria by antibiotic therapies [33,34].…”
Section: Bacterial Lipoproteins and Neuroinflammationmentioning
confidence: 99%
“…at the N-terminus of the peptide is responsible for immune activation and tissue injury [46,47], whereas the peptide portion of ospA is not effective at activating immune pathways [32]. Thus, tripalmitoyl-S-glyceryl-cysteine (Pam3-Cys), a synthetic lipopeptide mimicking the N-termini of osp, is often used for studying bacterial infection in a wide range of research fields involving immunology and neuroscience [48,49].…”
Section: Bacterial Lipoproteins and Neuroinflammationmentioning
confidence: 99%
See 1 more Smart Citation